Investigating Elements of Existential Nihilism in Seyyed Ali Hejazi Yazdi's Sherrir - ayoob moradi (مطالعات بین‌رشته‌ای ادبیات، هنر و علوم انسانی)
There is a strong connection between narration and philosophy both in its general sense, which means people's attitudes and worldviews and its specialized meaning, which refers to the systematic philosophy of professional philosophers. In the first sense of this connection, authors use the tool of narration to put forward their own thoughts, beliefs, feelings and judgments, and in the second sense, different narrative formats are used as tools to express philosophical concepts, similar to Camus's Myth of Sisyphus. The novel Sherrir by Seyyed Ali Hijazi Yazdi is an Iranian example of the second type of relationship between philosophy and narrative, in which the author has used the novel to express the concept of existential nihilism. Existential nihilism is one of the branches of nihilistic thought, which is based on absolute skepticism and rejection of accepted beliefs on issues such as the meaning of life, death, loneliness, love, etc. Based on this premise, the present paper aims to examine the ways in which this concept is described in the novel through an analytical-descriptive lens and drawing on the theoretical framework regarding the concept of nihilism. The results show that in this novel, the author has paid attention to topics such as futility, death, emptiness, disbelief in God, loneliness, boredom, and finally the tendency towards an illusory existence, all of which are narrativized aspects of the philosophical concept of existential nihilism.